2021
DOI: 10.3389/fpls.2021.729935
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Climate and Competition on Radial Growth, Recovery, and Resistance in Mongolian Pines

Abstract: Understanding the response of tree growth and drought vulnerability to climate and competition is critical for managing plantation forests. We analyzed the growth of Mongolian pines in six forests planted by the Three-North Shelter Forest Program with tree-ring data and stand structures. A retroactive reconstruction method was used to depict the growth-competition relationships of Mongolian pines during the growth period and their climatic responses under different competition levels. Drought vulnerability was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Studies of the radial growth of Scots pine in Mongolia and China have shown that the growth of natural forests was closely related to the climatic factors of the previous year, while the growth of plantation stands was associated with the climatic factors of the growing season of the current year (Sun et al, 2021). The study by French researchers has established that seedlings of black Pine (Pinus nigra ssp.…”
Section: Figure 6 Correlation Coefficients Between the Indices Of Ear...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the radial growth of Scots pine in Mongolia and China have shown that the growth of natural forests was closely related to the climatic factors of the previous year, while the growth of plantation stands was associated with the climatic factors of the growing season of the current year (Sun et al, 2021). The study by French researchers has established that seedlings of black Pine (Pinus nigra ssp.…”
Section: Figure 6 Correlation Coefficients Between the Indices Of Ear...mentioning
confidence: 99%
“…Dendrochronological methods are widely used in modern research on the dynamics of forest ecosystems, the response of plantings to climate change, and the assessment of plant damage and productivity (Huang et al, 2021;Soulé et al, 2021;Sun et al, 2021). Radial tree growth is a bioindicator that can be used to determine the level of forest damage, the response of trees to climate stress factors (Koval, 2020;Kipfmueller et al, 2022), increased lighting, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrochronological methods are widely used in modern research on the dynamics of forest ecosystems, the response of plantings to climate change, and the assessment of plant damage and productivity (Huang et al, 2021;Soulé et al, 2021;Sun et al, 2021). Radial tree growth is a bioindicator that can be used to determine the level of forest damage, the response of trees to climate stress factors (Koval, 2020;Kipfmueller et al, 2022), increased lighting, etc.…”
Section: Introductionmentioning
confidence: 99%